Analisis Return & Risiko Strategi Screening Saham Oleh Youtuber Indonesia - Kesuma, Franky (Keizai, 2025)
This study aims to prove whether the stock screening strategy provided by Indonesian YouTubers can give significantly higher returns compared to Indonesian market returns (IDX Composite). After forming 3 portfolios based on various screening criteria provided by 3 Indonesian Financial/Investment YouTubers, it was found that the returns of the three portfolios were not significantly higher than the IDX Composite returns for short-term or long-term investments. Although the portfolio's average return with the most stringent screening criteria appears to be greater than the IDX Composite, this is accompanied by a higher increase in value-at-risk and a consistently higher standard deviation than the IDX Composite. So the recommendations given by influencers may not just be formulated based on the most optimal screening strategy for their audience, but are also influenced by their interests.